Phenomena of Degree Completion in Distance Education: An Explanatory Case Study of Higher Education: Muhammad Jamil,Zafar Iqbal (PJDOL, 2023)
The number of students being enrolled in distance learning institutes is huge, which is a token of success for this mode of education. But literature showed that many students could not complete their degrees due to various reasons. Some of the reasons are common but can vary in different regions according to resources available and socio-economicconditions of learners. This study was designed to determine completionrate along with exploring factors affecting their degree completion. Mix method approach was used to conduct the study. Quantitative data was retrieved from admission office and controller office for ten years. Semistructured interviews were conducted from those students who could not complete their degrees.